Global environmental change : - Myers, Samuel S. (Worldwatch Institute, 2009)
Global climate change threatens human health in numerous and profound ways. Large segments of the population will experience more heat waves, altered exposure to infectious disease, and more-frequent natural disasters. Most significantly, climatic disruption threatens the adequacy of the core “building blocks” of health for large populations around the globe: sufficient food and nutrition, safe water for drinking and sanitation, fresh air to breathe, and secure homes to live in. As climate change dismantles these central elements of healthy societies, people with fewer resources will be forced to migrate in large numbers to lands where they may not be welcome. A likely result of all of these processes will be increased civic instability and strif